Perjanjian Nominee Antara Warga Negara Asing dengan Warga Negara Indonesia dalam Praktik Jual Beli Satuan Rumah Susun - Mahfi, Richi Al; Anggoro, Teddy (Wajah Hukum, 2025)
The practice of nominee agreements in the sale and purchase of apartment units between foreign nationals (WNA) and Indonesian citizens (WNI) which is based on the limited ownership of apartment units by WNA. And then it becomes a significant legal issue because when viewed from the legal aspect, it is found that the Nominee Agreement does not meet the objective requirements for the validity of an agreement, which results in the agreement being null and void according to the provisions of the laws and regulations in force in Indonesia. This also has a serious impact and is detrimental to many related parties, and provides legal uncertainty for the parties involved. WNA are not recognized as legal owners, while WNI who are nominees are vulnerable to legal sanctions. Nominee agreements also conflict with the principle of land sovereignty. Unclear regulations and weak law enforcement also worsen the situation. The purpose of this study is to analyze and determine the legality of nominee agreements based on legal regulations in Indonesia, as well as the impact of ownership of apartment units for the parties. Thus, it is known that to overcome this problem, comprehensive legal reform is needed, including regulations that provide legal certainty for all parties in carrying out legal actions, especially agreements, so that they remain within the appropriate legal corridor, without setting aside the principle of freedom of contract.